Earthquake engineering for dams and reservoirs - Hinks, Jonathan (Emerald Publishing Limited, 2023)
Earthquake Engineering Blurb With contributions from many distinguished specialists from around the world, Earthquake Engineering for Dams and Reservoirs addresses all topics that will be of interest to students and professionals involved in the inspection or design of dams in seismic areas. Over recent years, research has developed rapidly in response to incidents worldwide where earthquakes have, either directly or indirectly, affected dams or their appurtenant structures. This title brings relevant data together in one well-collated volume of need-to-know information. It will help you to make decisions on the type of dam structure required for new projects and understand the issues that face existing dams and how to mitigate them. With international case studies, in full colour, from regions with differing seismic activity levels, this book features coverage of * plate tectonics * seismic input parameters * reservoir triggered seismicity * seismic design and performance criteria * dams of various types including rockfill, concrete, earthfill, liquefaction, dams of hydraulic fill and tailing dams * Dams on active faults * spillways, gates and equipment * earthquake-triggered landslides, rockfalls, seismic seiches and instrumentation. This is essential reading for any engineer, or designer, tasked with building, retrofitting or maintaining dams in all seismically active regions. It will also appeal to dam owners and managers, writers of feasibility studies and students of engineering.
Includes index.
Keywords: Earthquake engineering.; Dams -- Earthquake effects.; Reservoirs -- Earthquake effects.; Technology & Engineering -- Civil / Earthquake.; elektronické knihy; electronic books